2016
DOI: 10.1109/taslp.2016.2526779
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Time-Frequency Analysis for Noise Reduction in an Audio Filter Bank With Low Delay

Abstract: In this paper, an adaptive time-frequency analysis scheme is proposed along with a synthesis scheme using an asymmetric window. The proposed scheme is suitable for audio noise reduction with a low delay in the range of 0 to 4 ms. The main novelty of the paper is the adaptive analysis scheme that can adapt to the incoming signal independently in both time and frequency by employing a complex filter on a DFT modulated filter bank. A number of adaptive time-frequency schemes are described that are suitable for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, software filtering is commonly reliant on cut-off frequencies which can be precisely controlled by consenting implementation of innovative filter models. The signal levels are enormously small (i.e., 1 mV for bio-signals such as ECG), and it is crucial to apply filtering to eradicate a wide range of unwanted noisy signals [ 8 , 37 , 38 , 39 , 40 ]. The noise in ECG signal is mainly due to unstable DC offset between the electrode–human body interaction, electrical instrumental noise in the environment, power-line (50/60 Hz), muscle noise, and internal noise while manufacturing wearable ECG devices [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, software filtering is commonly reliant on cut-off frequencies which can be precisely controlled by consenting implementation of innovative filter models. The signal levels are enormously small (i.e., 1 mV for bio-signals such as ECG), and it is crucial to apply filtering to eradicate a wide range of unwanted noisy signals [ 8 , 37 , 38 , 39 , 40 ]. The noise in ECG signal is mainly due to unstable DC offset between the electrode–human body interaction, electrical instrumental noise in the environment, power-line (50/60 Hz), muscle noise, and internal noise while manufacturing wearable ECG devices [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The parameters individually showed best performance having optimum values. IEEE members Andersen and Marc [ 40 ] propose an adaptive time-frequency analysis scheme using an asymmetric window. This technique is suitable for audio noise reduction in the low delay of 0–4 ms and has less computational complexity.…”
Section: Related Workmentioning
confidence: 99%
“…Departing from the tradition of symmetric analysis and synthesis windows that have the same duration, asymmetric windowing allows us to simultaneously achieve high spectral resolution and low latency by combining long analysis windows with short synthesis windows. The asymmetric windows we use in this work have been adapted from [23], though other asymmetric windowing approaches can be found in the literature [37]- [40].…”
Section: B Asymmetric Stft Windowingmentioning
confidence: 99%
“…Evaluating the ztransforms on the unit circle, the higher frequency resolution in X l (z) implies that h L [n] has a more narrow lowpass frequency response than h K [n] and that L > K. It has been shown that WOLA filter banks with longer prototype filters, such as h L [n], can still be synthesized with the same low delay as h K [n], see for instance [12], [13], [14]. The HRFB gives an improved frequency resolution representation of x[n] under the assumption that the signal is stationary over L samples.…”
Section: Background and Problem Statementmentioning
confidence: 99%